Promoting Accurate Variability of Social Skills in Children With Autism Spectrum Disorder. (January 2017) - Radley, Keith C.; Dart, Evan H.; Moore, James W.; Battaglia, Allison A.; LaBrot, Zachary C.
Restricted and repetitive behavior is a central feature of autism spectrum disorder (ASD), with such behaviors often resulting in lack of reinforcement in social contexts. The present study investigated training multiple exemplars of target behaviors and the utilization of lag schedules of reinforcement in the context of social skills training to promote appropriate and varied social behavior in children with ASD. Five participants with ASD between the ages of 7 and 9 attended a twice-weekly social skills group for 8 weeks. A multiple probe design across skills was utilized to assess intervention effects. During baseline, participants demonstrated low levels of skill accuracy and low appropriate variability in responding. During continuous reinforcement with one trained exemplar, skill accuracy increased while appropriate variability remained low. Training of three exemplars of target skills resulted in minimal improvements in appropriate variability. Introduction of a Lag 2 schedule with three trained exemplars was generally associated with increased appropriate variability. Further appropriate variability was observed during Lag 4 with three trained exemplars. Limitations and implications are discussed.